Long-Time Treatment by Low-Dose N-Acetyl-L-Cysteine Enhances Proinflammatory Cytokine Expressions in LPS-Stimulated Macrophages - Ohnishi, Tomokazu; Bandow, Kenjiro; Kakimoto, Kyoko; Kusuyama, Joji; Matsuguchi, Tetsuya (PLOS ONE, 2014)
N-acetyl-L-cysteine is known to act as a reactive oxygen species scavenger and used in clinical applications. Previous reports have shown that high-dose N-acetyl-L-cysteine treatment inhibits the expression of proinflammatory cytokines in activated macrophages. Here, we have found that long-time N-acetyl-L-cysteine treatment at low-concentration increases phosphorylation of extracellular signal-regulated kinase 1/2 and AKT, which are essential for the induction of proinflammatory cytokines including interleukin 1β and interleukin 6 in lipopolysaccharide-stimulated RAW264.7 cells. Furthermore, long-time N-acetyl-L-cysteine treatment decreases expressions of protein phosphatases, catalytic subunit of protein phosphatase-2A and dual specificity phosphatase 1. On the other hand, we have found that short-time N-acetyl-L-cysteine treatment at low dose increases p53 expression, which inhibits expressions of proinflammatory cytokines. These observations suggest that long-time low-dose N-acetyl-L-cysteine treatment increases expressions of proinflammatory cytokines through enhancement of kinase phosphorylation.